(3ELGHI Yf SDGd Yf MOjK (B" (3dh YGT EHQGgje dcGf fHjG (B"s - (3eMeO GdJGhOj Hf eMeO GdWGdH Hf eMeO Hf Ydj GHf ShOg GdeQj,J (B1209 (3g` s
(3ChdgG (B:s
(3hHYO abO SFdJ Yf MOjK dh YGT EHQGgje dcGJ fHjkG s
(3BNQgG (B:s
(3hjMUd GdYbd Hge hjced hGddg jdge GdLhGH hGddg CYde HMGdg s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B62 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B125s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(609 (3d(B) s
Keywords: (3GdMOjK h GdeUWdMs